PENGARUH STRATIFIKASI SUHU RENDAH DAN KRIOPROTEKTAN TERHADAP VIABILITAS BENIH ROSELA (Hibiscus sabdariffa L.) - Dede Suhendra (JURNAL AGROPLASMA, 2019)
The objective of the research was to know effect of treatment low temperature and cryoprotectants, and combination to seed viability of rosele. The research was conducted at the Seed Technology Laboratory, Agriculture Faculty, University of Sumatera Utara, Medan with height ± 25 meters above sea level, in January to February 2014, using a randomized block design with 4 level low temperature stratification and cryoprotectants treatment as well combination and control. Parameters observed were moisture content seed (%), germination rate (day), germination normal (%), abnormal sprouts (%), seeds die (%), vigor index (%), wet weight of sprouts (g), dry weight of sprouts (g). The results showed that rosele seed viability using provision cryoprotectants and cooling rate -5°C the best result in treatments other. Keywords: seed rosele, low temperature stratification, cryoprotectans